THE INFLUENCE OF PRICE AND PRODUCT QUALITY ON PURCHASE DECISIONS FOR DAIRY PRODUCTS KRUCIL KRUCIL ARGOPURO PROBOLINGGO - Yayuk Indah Wahyuning Tyas; Agung Yatiningrum (LPPM Press STIE Indragiri Rengat, 2021)
This research was conducted at the Krucil KUD Milk House with the research objectives to be achieved: (1) to determine simultaneously the significant effect of price and product quality on purchasing decisions at Krucil Argopuro Probolinggo KUD Milk House. (2) to find out partially the significant effect of price and product quality on purchasing decisions at the Krucil Argopro Probolinggo KUD Milk House. (3) to find out between the price and product quality variables that have a dominant influence on purchasing decisions at the Krucil Argopuro Probolinggo KUD Milk House. The population in this study were all consumers during the last 1 year as many as 7,241 people with samples taken using the Slovin formula as many as 100 people. By using a sampling technique that is random sampling. The type of research used in this research is quantitative research. The variables used include price, product quality, and purchasing decisions. The data analysis method from the research results is the quantitative description method using SPSS in the form of validity and reliability tests, classical assumption tests, multiple regression analysis, coefficient of determination, hypothesis testing. The results of the study are shown by multiple regression equations proving that price and product quality have a significant effect on purchasing decisions. And the results of partial hypothesis testing prove that price and product quality have a significant effect on purchasing decisions. The results of the dominant hypothesis test show that the X2 variable has a higher tcount value than the other independent variables.